SERUM OESTRADIOL LEVEL DURING MATING AND ITS EFFECT ON CONCEPTION RATE IN THE ALPACA - Díaz C., Arturo (2011)
The aim of the study was to determine the serum oestradiol level in adult alpacas during the first post-partum mating and its effect on conception rate. It was selected 85 non-lactating female adult alpacas without calf at foot. Sexual receptive females were mated with a male of proven fertility. Blood samples were collected at mating and the level of oestradiol in serum was determined by radioimmunoassay. Conception was determined by ultrasound at 25-27 days of mating. Oestradiol values were distributed in two groups: A (<0.5 pg/mL) and B (>0.5 pg/mL), where the mean was 0.78 ± 0.39 pg/mL. Conception rate in alpacas with low oestradiol level at time of mating was 52.5% and in alpacas with high level was 66.7% without significant difference. Results indicate the lack of influence of oestradiol levels on conception rate.